THE EFFECT OF FINANCING OR CREDIT RISK, LIQUIDITY AND CAPITAL ADEQUACY ON THE PROFITABILITY OF ISLAMIC BANKS IN 2016-2021 - Dzar Lathuf Farassi; Slamet Haryono (SEAN Institute, 2023)
In Indonesia, there are two types of banking operations: conventional and sharia. The existence of these two types of banks has a positive impact, namely the emergence of motivation to improve their performance better than other banks. The purpose of this research was to find out how the influence of financing or credit risk, liquidity risk, and capital adequacy risk have affected the profitability of Islamic banking in Indonesia in 2017–2021, both partially and simultaneously. This research uses a type of quantitative-descriptive research. The conclusion that can be drawn from this study is that the variables of financing or credit risk, liquidity risk, and capital adequacy risk significantly influence profitability. In the t (partial) test, the financing or credit risk variable has a significant effect on the profitability of Islamic banking in 2016–2021. The t (partial) test of the liquidity risk variable has no effect on the profitability of Islamic banking in 2016–2021. And the partial t test for capital adequacy risk has a significant effect on the profitability of Islamic banking in 2016–2021.